1983
DOI: 10.1136/gut.24.10.940
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis: geographical clustering and symptomatic onset seasonality.

Abstract: SUMMARY Patients with primary biliary cirrhosis (primary non-suppurative destructive cholangitis) in the north east region of England were studied over a five year period and, to evaluate epidemicity, compared with two contemporaneous disease series of known occurrence. These were: terminal renal failure, all causes (low or absent epidemicity n= 106) and an outbreak of echovirus 19 disease (high epidemicity n=201). Eight primary biliary cirrhosis-affected men and 109 women from an estimated catchment populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 14 publications
2
39
2
Order By: Relevance
“…Studies from the UK indicate that such frequency ranges between 1 and 2.4%, 8,9 possibly increasing over the past decade, likely for the awareness of physicians and novel diagnostic tools. In the United States, Bach and Schaffner 10 observed a 4.3% familial prevalence in an analysis of 396 PBC cases both retrospectively and prospectively.…”
Section: Familial Pbcmentioning
confidence: 99%
“…Studies from the UK indicate that such frequency ranges between 1 and 2.4%, 8,9 possibly increasing over the past decade, likely for the awareness of physicians and novel diagnostic tools. In the United States, Bach and Schaffner 10 observed a 4.3% familial prevalence in an analysis of 396 PBC cases both retrospectively and prospectively.…”
Section: Familial Pbcmentioning
confidence: 99%
“…11 Treatment with various drugs including chlorpromazine, prochlorperazine, and estrogens has also been linked anecdotally with PBC. [12][13][14] Our observation of a large series of PBC patients and published associations with similar diseases suggested that recent surgeries and lifestyle factors, such as smoking, drinking, stressful life events, and pet ownership, would also be worth exploring. Other etiological factors for PBC have been suggested, but we concentrated on those that could be investigated by a self-completion questionnaire.…”
mentioning
confidence: 99%
“…Lastly, several studies have shown that the prevalence of PBC within families of affected individuals is significantly higher than in the general population. 13,16 Differences in the local prevalence of PBC have been reported [7][8][9][10]17,18 and may reflect differences in exposure to environmental toxins. However, strong linkage to any specific environmental factor has not been identified except in a Japanese study 18 showing an increased prevalence of PBC in Hiroshima among atomic bomb survivors.…”
mentioning
confidence: 99%
“…5,6 Large geographic variations in the prevalence of PBC have been reported. [7][8][9][10] Differences in both genetic susceptibility factors and exposure to environmental toxins are widely believed to contribute to this variability in the prevalence of PBC.…”
mentioning
confidence: 99%